Infantile Hemangioma and Updated Recommended Treatment - Silva, Maria João (2019)
Infantile hemangioma is a benign vascular tumor that frequently occurs at pediatric age, normally at a rate of 2% to 12% in Caucasian newborn babies, particularly in females. The International Society for The Study of Vascular Anomalies has divided these anomalies into two categories: vascular tumors and vascular malformations, including infantile hemangioma among benign vascular tumors. Clinical evolution is characteristic, and consists of a proliferative phase and a spontaneous involution phase. Diagnosis is usually clinical, but sometimes other diagnostic procedures may eventually be necessary. The majority of infantile hemangioma has a favorable outcome and spontaneous resolution. However, in some cases there are local or systemic complications, with the need for additional therapeutic intervention in case of vital, functional or esthetic risks. Oral propranolol is the current treatment of choice for infantile hemangioma, being the only treatment internationally approved for this indication. It should be started as early as possible to maximize efficacy and avoid potential complications. Other therapeutic options can be considered as a second choice, such as oral, topical or intralesional corticosteroids, topical beta-blockers, pulsed-dye laser or surgery.